2016
DOI: 10.1093/sleep/zsw043
|View full text |Cite
|
Sign up to set email alerts
|

Sexsomnia: A Specialized Non-REM Parasomnia?

Abstract: In this single-center series, we confirmed the male predominance of sexsomnias and its potential for severe clinical and forensic consequences. The results suggest a continuum of regular sleepwalking, sleepwalking with occasional sexsomnia, and quasi-exclusive sexsomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 17 publications
0
45
0
4
Order By: Relevance
“…In 2015, Schenk 5 published an update with 22 additional patients diagnosed with sexsomnia. Another case series with 41 patients was published in 2016 by Muza et al 6 In 2017, Dubessy et al 7 reported 17 additional cases of sexsomnia. Summarizing the previously published reports, it is clear that sexsomnia may be manifested in many different ways.…”
Section: Discussionmentioning
confidence: 98%
“…In 2015, Schenk 5 published an update with 22 additional patients diagnosed with sexsomnia. Another case series with 41 patients was published in 2016 by Muza et al 6 In 2017, Dubessy et al 7 reported 17 additional cases of sexsomnia. Summarizing the previously published reports, it is clear that sexsomnia may be manifested in many different ways.…”
Section: Discussionmentioning
confidence: 98%
“…É um comportamento preponderantemente dirigido para a região genital. A sexsônia tem sido considerada prevalecente no sexo masculino (DEBUSSY et al, 2017;SCHENCK, 2015). As mulheres costumam apresentar masturbação e sonilóquio sexual (ARIÑO et al, 2014) e os homens, carícias sexuais e penetração sexual como categorias desse comportamento (YEH; SCHENCK, 2016).…”
Section: Sexsôniaunclassified
“…A sexsônia é uma real condição clínica que compromete o paciente e quem está dormindo ao seu lado. O relato de 17 casos em clínica de sono (DEBUSSY et al, 2017) considera o impacto psicossocial na vida dos envolvidos (depressão, tentativa de suicídio, pedidos de divórcio, perda da custódia de filhos, acusação de estupro). Desta forma, muitos dos casos podem resultar em ações criminais como é o caso de um mecânico de 32 anos, desempregado e usuário constante de drogas.…”
Section: Consequênciasunclassified
See 2 more Smart Citations